Taxpayer Awareness and Knowledge Boost Tax Compliance during COVID-19: Role of Socialization: Kesadaran dan Pengetahuan Wajib Pajak Tingkatkan Kepatuhan Pajak Selama COVID-19 Peran Sosialisasi - Shoffan, Muchammad Abi; Ernandi, Herman (Indonesian Journal of Law and Economics Review, 2023)
The aim of this study is to investigate the influence of taxpayer attitude, awareness, and tax knowledge on tax compliance during the COVID-19 pandemic, with tax socialization as a moderating variable. The study focuses on 33 businesses registered under the Indonesian Contractor and Mechanical Association (AKLI) Sidoarjo branch in 2022, using purposive sampling criteria. The SmartPLS (Partial Least Square) analysis was used to analyze the data. The results indicate that taxpayer attitude does not significantly affect tax compliance, while taxpayer awareness and tax knowledge do have an impact. Tax socialization moderates taxpayer awareness but does not moderate taxpayer attitude or tax knowledge on tax compliance. The study implies that tax authorities should prioritize tax socialization programs to increase taxpayer awareness and ultimately improve tax compliance during the COVID-19 pandemic. Highlights: Taxpayer awareness and knowledge have a significant impact on tax compliance during the COVID-19 pandemic. Tax socialization moderates taxpayer awareness but does not affect taxpayer attitude or tax knowledge on tax compliance. Tax authorities should prioritize tax socialization programs to increase taxpayer awareness and ultimately improve tax compliance during the COVID-19 pandemic.